Neglected tropical diseases among the Association of Southeast Asian Nations (ASEAN): overview and update. - Peter J Hotez; Maria Elena Bottazzi; Ulrich Strych; Li-Yen Chang; Yvonne A L Lim; Maureen M Goodenow; Sazaly AbuBakar (Public Library of Science (PLoS), 2015)
The ten member states of the Association of Southeast Asian Nations (ASEAN) constitute an economic powerhouse, yet these countries also harbor a mostly hidden burden of poverty and neglected tropical diseases (NTDs). Almost 200 million people live in extreme poverty in ASEAN countries, mostly in the low or lower middle-income countries of Indonesia, the Philippines, Myanmar, Viet Nam, and Cambodia, and many of them are affected by at least one NTD. However, NTDs are prevalent even among upper middle-income ASEAN countries such as Malaysia and Thailand, especially among the indigenous populations. The three major intestinal helminth infections are the most common NTDs; each helminthiasis is associated with approximately 100 million infections in the region. In addition, more than 10 million people suffer from either liver or intestinal fluke infections, as well as schistosomiasis and lymphatic filariasis (LF). Intestinal protozoan infections are widespread, while leishmaniasis has emerged in Thailand, and zoonotic malaria (Plasmodium knowlesi infection) causes severe morbidity in Malaysia. Melioidosis has emerged as an important bacterial NTD, as have selected rickettsial infections, and leptospirosis. Leprosy, yaws, and trachoma are still endemic in focal areas. Almost 70 million cases of dengue fever occur annually in ASEAN countries, such that this arboviral infection is now one of the most common and economically important NTDs in the region. A number of other arboviral and zoonotic viral infections have also emerged, including Japanese encephalitis; tick-borne viral infections; Nipah virus, a zoonosis present in fruit bats; and enterovirus 71 infection. There are urgent needs to expand surveillance activities in ASEAN countries, as well as to ensure mass drug administration is provided to populations at risk for intestinal helminth and fluke infections, LF, trachoma, and yaws. An ASEAN Network for Drugs, Diagnostics, Vaccines, and Traditional Medicines Innovation provides a policy framework for the development of new control and elimination tools. Together with prominent research institutions and universities, the World Health Organization (WHO), and its regional offices, these organizations could implement important public health improvements through NTD control and elimination in the coming decade.